2017
DOI: 10.2147/opth.s128453
|View full text |Cite
|
Sign up to set email alerts
|

Preservative-free fixed combination of tafluprost 0.0015% and timolol 0.5% in patients with open-angle glaucoma and ocular hypertension: results of an open-label observational study

Abstract: BackgroundEfficacy, tolerability and safety of the novel preservative-free fixed combination of tafluprost 0.0015%/timolol 0.5% (Taptiqom®) were investigated in an observational study in Germany.ObjectiveTo assess efficacy, tolerability and safety of the preservative-free fixed combination of tafluprost 0.0015%/timolol 0.5% in a real-life setting.MethodsIntraocular pressure (IOP) was recorded for each eye at baseline (any previous therapy or untreated) and 4–16 weeks after changing medical treatment to or init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…Regardless of the prior monotherapy subgroup, statistically and clinically significant IOP reductions were present from Week 4 and sustained over the 6-month study period. These data are reflective of the primary VISIONARY publication and of other real-world data concerning IOP-lowering efficacy with PF tafluprost/timolol FC following a switch away from different topical glaucoma medications [ 22 , 23 ]. Emerging country-level data from the VISIONARY study has revealed differences in baseline IOP, with clinicians in some countries selecting patients with higher IOPs for inclusion in the study [ 31 – 34 ].…”
Section: Discussionmentioning
confidence: 85%
“…Regardless of the prior monotherapy subgroup, statistically and clinically significant IOP reductions were present from Week 4 and sustained over the 6-month study period. These data are reflective of the primary VISIONARY publication and of other real-world data concerning IOP-lowering efficacy with PF tafluprost/timolol FC following a switch away from different topical glaucoma medications [ 22 , 23 ]. Emerging country-level data from the VISIONARY study has revealed differences in baseline IOP, with clinicians in some countries selecting patients with higher IOPs for inclusion in the study [ 31 – 34 ].…”
Section: Discussionmentioning
confidence: 85%
“…Again, there was no significant difference between our findings and those of the above-mentioned studies [ 5 , 6 ]. However, the previous studies that investigated in patients with glaucoma and OH reported that the width and rate of IOP reduction were 3.6–5.1 mmHg and 18.0–24.0% during 4–16 weeks of follow-up [ 7 ] and 2.5 mmHg and 15.0% during 3 months of follow-up [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…TTFC has demonstrated efficacy and safety in reducing IOP in some studies [ 5 - 11 ]. However, with the exception of some studies in Japan [ 5 , 6 , 8 ] and one study in Germany [ 7 ], direct comparisons of switching from tafluprost to TTFC are limited. The efficacy and safety of TTFC have been investigated in patients with all types of glaucoma and Ocular Hypertension (OH) [ 7 , 8 ], but there are no reports on the efficacy and safety of TTFC in Japanese patients with primary open-angle glaucoma (POAG).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Suatu studi observasional juga menunjukkan hasil serupa yaitu kombinasi tanpa pengawet terfiksir dari tafluprost 0,0015% dan timolol 0,5% sangat efektif dan aman bagi pasien glaukoma sudut terbuka. 21 Kedua, bimatoprost yang diadministrasi QOD-HS lebih efektif untuk mengontrol TIO pada pasien PEG yang memiliki masalah efek samping dengan bimatoprost 0,03% QHS. Belum ada studi lain dengan topik serupa untuk dilakukan komparasi.…”
Section: Pembahasanunclassified

Terapi Pseudoexfoliation Glaucoma

Wirananda Setiawan,
Suryaningrum,
Sutyawan
et al. 2022
eum